HEERAMANDI: A CRITICAL REVIEW ON THE ROLE OF THE COURTESANS IN INDIA'S INDEPENDENCE STRUGGLE - Patnaik, Sudhir Kumar; Gouda, Nikhil Kumar; R, Rijitha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Media played an important role in disseminating the anti-colonial sentiments during India's freedom movement. Many cultural shows, dramas, and local festivals were used as a medium to spread secret messages and unite people against the British. Women, particularly the courtesans (tawaifs), contributed significantly through their unique social and artistic positions. Heeramandi: The Diamond Bazaar (2024) dramatizes these contributions, fusing fact with fiction to demonstrate how artistic expression functioned as a vehicle for rebellion. This paper explores the portrayal of courtesans as agents of alternative media and evaluates the balance between historical accuracy and cinematic romanticization.